Respuesta :

Step-by-step explanation:

Following B. O. D. M. A. S rule :

= { [ 8 / 2] ^2 - 6} * (-2)

= { 4 ^ 2 - 6} * - 2

= 10 * - 2

= - 20

Answer:

Solution : - 20

Step-by-step explanation:

We have the following expression to simplify,

[tex]\left\{\left[\frac{\left(3+5\right)}{2}\right]^2-\left(3\cdot 2\right)\right\}\cdot \left(-2\right)[/tex]

Let's start by simplifying simple expressions, such as 3 + 5 = 8 and 3 * 2 = 6. Substituting we receive,

[tex]\left\{\left[\frac{\left(8\right)}{2}\right]^2-\left(6\right)\right\}\cdot \left(-2\right)[/tex]

8 / 2 = 4, and 4² = 16 -

[tex]\left\{16-\left(6\right)\right\}\cdot \left(-2\right)[/tex]

And of course 16 - 6 = 10, simplifying the expression to " - 2 [tex]*[/tex] 10 " leaving us with a solution of - 20.

ACCESS MORE